PEMBERIAN HAK ASIMILASI KEPADA NARAPIDANA DI LEMBAGA PEMASYARAKATAN KELAS I KEDUNGPANE SEMARANG - Abdul Nasir; Safik Faozi (Fakultas Hukum Universitas Stikubank, 2021)
This assimilation can be a measure of success carried out by the correctional institution, because it is a process of increasing coaching based on the evaluation of previous coaching programs and has gone through certain assessments and has met the requirements set by the Correctional Team. The author is interested in the problem of assimilation guidance for prisoners at the Kedungpane Class I Prison in Semarang and the obstacles in the assimilation guidance program for inmates. This study uses a juridical empirical or sociological juridical approach. The results of the research and discussion are that assimilation is carried out for the development of prisoners in socializing in the community. In addition, Assimilation is also carried out in the context of tackling the Spread of Covid-19 that is currently hitting Indonesia. The obstacle in fostering the assimilation of prisoners is the lack of socialization to the community so that there are no third parties or people who are willing to accept and employ prisoners in the process of returning to society in a positive way. Keywords : assimilation, Correctional Institution, convict .